2022
DOI: 10.1097/md.0000000000029853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of preanalytical errors in a clinical chemistry laboratory: A 2-year study

Abstract: Patient safety and medical diagnosis of patients are mainly influenced by laboratory results. The present study aimed to evaluate the errors in the preanalytical phase of testing in a Clinical Chemistry diagnostic laboratory. A review was conducted at the Clinical Chemistry Laboratory of a hospital in Saudi Arabia from January 2019 to December 2020. Using the laboratory information system, the data of all canceled tests and requests were retrieved and evaluated for preanalytical errors. A total of 55,345 labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
1
4
1
Order By: Relevance
“…This finding is nearly similar to a study conducted at the Cantonal Hospital Zenica in Bosnia and Herzegovina, which found that 11.63 % [ 19 ] of samples were rejected due to insufficient quantity. However, this result is higher than the findings of a study conducted at the University of Gondar Hospital in Northwest Ethiopia, 0.1 % [ 15 ]; Saudi Arabia, 1.7 % [ 14 ]; India, 0.2 % [ 28 ]; and India, 1.6 % [ 27 ]. On the other side, our study's findings are lower than the result of the study done in Oromia, Ethiopia, 23.3 % [ 25 ], and Libya, 50 % [ 23 ] of samples were rejected due to insufficient quantity.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…This finding is nearly similar to a study conducted at the Cantonal Hospital Zenica in Bosnia and Herzegovina, which found that 11.63 % [ 19 ] of samples were rejected due to insufficient quantity. However, this result is higher than the findings of a study conducted at the University of Gondar Hospital in Northwest Ethiopia, 0.1 % [ 15 ]; Saudi Arabia, 1.7 % [ 14 ]; India, 0.2 % [ 28 ]; and India, 1.6 % [ 27 ]. On the other side, our study's findings are lower than the result of the study done in Oromia, Ethiopia, 23.3 % [ 25 ], and Libya, 50 % [ 23 ] of samples were rejected due to insufficient quantity.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the overall sample rejection at the pre-analytical phase in the current study is higher than the studies conducted at Amhara Public Health Institute in Bahir Dar, Ethiopia, 0.5 % [ 9 ]; St. Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia, 1.4 % [ 1 ]; Delhi, 1.52 % [ 18 ]; Cantonal Hospital Zenica, 1.7 % [ 19 ]; and Makkah, Saudi Arabia, 1.3 % [ 20 ]. On the other hand, our study's finding indicates a lower rate of overall sample rejection in the pre-analytical phase compared to the rate of overall pre-analytical sample rejection of previous studies conducted at St. Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia,26 % [ 2 ]; St. Paul's Hospital Millennium Medical College (SPHMMC) in Addis Ababa, Ethiopia,72.3 % [ 21 ], and Saudi Arabia, 12.1 % [ 14 ]. This difference could be attributed to the sample size difference, workload, and not adhering to standard specimen collection procedures.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“… 1 It is essential to comprehend and acknowledge the origins of these errors to effectively address unexpected laboratory results which do not align with clinical information. 2 A myriad of causes may exist. Sometimes, even, the specific circumstances at the regional level, such as pandemics, possess the capacity to amplify the rate of pre-analytical errors.…”
Section: Introductionmentioning
confidence: 99%